1991
DOI: 10.1128/aem.57.8.2229-2232.1991
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Growth of Microorganisms with Chlorate as an Electron Acceptor

Abstract: The ability of microorganisms to use chlorate (C103) as an electron acceptor for respiration under anaerobic conditions was studied in batch and continuous tests. Complex microbial communities were cultivated anaerobically in defined media containing chlorate, all essential minerals, and acetate as the sole energy and carbon source. It was shown that chlorate was reduced to chloride, while acetate was oxidized to carbon dioxide and water and used as the carbon source for synthesis of new biomass. A biomass yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 9 publications
(10 reference statements)
2
20
0
Order By: Relevance
“…Although no chlorate or chlorite accumulated in the bottle, the chloride concentration increased by 143.2 mg/L (4.04 mM), accounting for 95% of the perchlorate decrease in the bottle. This is consistent with other biological perchlorate reduction research found in the literature, which has demonstrated complete microbial conversion of perchlorate to chloride (Coates et al, 1999;Herman & Frankenberger, 1999;Rikken et al, 1996;Attaway & Smith, 1993;Malmqvist et al, 1991).…”
Section: Figuresupporting
confidence: 92%
“…Although no chlorate or chlorite accumulated in the bottle, the chloride concentration increased by 143.2 mg/L (4.04 mM), accounting for 95% of the perchlorate decrease in the bottle. This is consistent with other biological perchlorate reduction research found in the literature, which has demonstrated complete microbial conversion of perchlorate to chloride (Coates et al, 1999;Herman & Frankenberger, 1999;Rikken et al, 1996;Attaway & Smith, 1993;Malmqvist et al, 1991).…”
Section: Figuresupporting
confidence: 92%
“…The optimum temperature for the bacterial bromate reduction is most probably above 20ЊC (Table 4). Malmqvist et al (19) found a reduction of 110 mg of ClO 3…”
Section: Discussionmentioning
confidence: 97%
“…are also able to reduce chlorate (ClO 3 Ϫ ) (18) and selenate (SeO 4 2Ϫ ) (16,17). Chlorate is an effective electron acceptor for bacteria (19), and it is likely that bromate is used in the same way. This hypothesis is supported by the observation that bromate removal stagnated in the absence of ethanol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ClO À 2 ! O 2 þ Cl À [5][6][7][8][9][10]. The first two steps are catalyzed by perchlorate reductase, and are relatively slower than the last step [5,11].…”
Section: Introductionmentioning
confidence: 99%